Theoretical and experimental research on long life prediction of the locking system of the space station docking mechanism - Lingxiao Quan; Jing Gao; Changhong Guo; Huiling Yuan (Scientific Reports)
Abstract This paper conducts theoretical and experimental research on the docking lock of the space station docking mechanism, aiming to predict its long-term service life. By analyzing the working principle and load transmission path of the docking lock, a theoretical model based on the material performance degradation mechanism is established, and the life degradation equation of key components under service conditions is derived. Additionally, accelerated performance degradation tests with temperature as the accelerated stress were conducted to validate the accuracy of the theoretical model. The results show that the life prediction error of the theoretical model is less than 5%, demonstrating that the docking lock can operate safely for over 15 years. Through stress relaxation and creep tests, relevant parameters were fitted, and numerical calculations and experimental verification confirmed that when the initial load is 37 kN, the attenuation value of the locking force after 15 years of service is less than 10%, and the remaining locking force still meets the safety service requirements. These findings provide crucial insights into the design and optimization of docking locks, providing technical support for the design of docking mechanisms for future space stations and other spacecraft, and have important engineering application value.